Formalni in dejanski delodajalec s poudarkom na novejši sodni praksi Vrhovnega sodišča - Vujanović Stepan, Sanja (Podjetje in delo, 2023)
In this article, I present the distinction between formal and actual employers, which is relevant in tripartite employment relationships where, in addition to the formal employer, there are one or more other entities that affect workers' rights. The distinction between formal and actual employer arises in a disguised employment relationship, where the relationship between the worker and the employer is outwardly presented differently than it is. The purpose is to nullify or reduce the protection provided to workers or to avoid paying taxes and contributions. In more recent case law, the Supreme Court, assessing the business model of the Port of Koper in the case of the IPS workers, has held that a disguised employment relationship is not only a relationship that gives the appearance of a different relationship existing between the parties with the intention of reducing legal protection, but also a relationship which outwardly exists between two parties, but is in fact carried out between the other parties, with the intention of reducing the rights and legal protection. Moreover, the Court has ruled that Articles 13 and 18 of the Employment Relationships Act are not intended only for those who are not in an employment relationship, but that legal protection for workers must also be ensured in the cases where the contractual performance of workers' obligations would unjustifiably deprive them of their rights. Furthermore, the Court has answered the question of whether, in the event of competition between two employment relationships, it is possible to intervene in the already established employment relationship and the acquired rights retroactively, while defining the liability of the actual employer for any disadvantages suffered by the worker during the existence of the disguised employment relationship.
Keywords: delodajalec; delovna razmerja; delovno pravo; sodna praksa; varstvo delavcev; Vrhovno sodišče